2019
DOI: 10.1002/pmrj.12196
|View full text |Cite
|
Sign up to set email alerts
|

Training and Practice Patterns in Cancer Rehabilitation: A Survey of Physiatrists Specializing in Oncology Care

Abstract: Background Cancer rehabilitation is an integral part of the continuum of care for survivors. Due to the increasing number of survivors, physiatrists commonly see cancer patients in their general practices. Essential to guiding the field is to understand the current training and practice patterns of cancer rehabilitation physicians. Objectives To assess current trends in training and practice for cancer rehabilitation physicians, including the level of burnout among providers in this field. Design Cross‐section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…2 Physiatrists have suggested that to further augment this education, there should be an emphasis on early mentorship and exposure to the potential of cancer rehabilitation fellowship. 3 We agree that there is a need to emphasize and organize cancer rehabilitation education, and the Vargo et al article supports this. Importantly, enhanced education will also require strong mentorship.…”
Section: Dear Editormentioning
confidence: 80%
“…2 Physiatrists have suggested that to further augment this education, there should be an emphasis on early mentorship and exposure to the potential of cancer rehabilitation fellowship. 3 We agree that there is a need to emphasize and organize cancer rehabilitation education, and the Vargo et al article supports this. Importantly, enhanced education will also require strong mentorship.…”
Section: Dear Editormentioning
confidence: 80%
“…With its emergent burgeoning activity, 1 various professional aspects of cancer rehabilitation have begun to receive attention, including physiatrist practice patterns, 2 physician workforce training expectations, 3,4 and the roles of cancer rehabilitation team members 5 . However, vast challenges remain in optimizing availability and integration of rehabilitation services for the millions of cancer patients and survivors 6 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Although these disability and cancer prevalence estimates are independent, clinicians have recognized increasingly that cancer and its treatment can be profoundly disabling, often causing neurologic or musculoskeletal impairments requiring rehabilitation therapy. [4][5][6] In 2017, 2.8% of beneficiaries receiving Social Security Disability Insurance qualified because of cancer-related disability. 7 The Social Security Administration's Compassionate Allowances offers fast-track approval of disability benefits for person with progressive cancer.…”
Section: Introductionmentioning
confidence: 99%